PENGARUH PELATIHAN COACHING UNTUK MENINGKATKAN KINERJA SUPERVISOR PADA DIVISI WIRANIAGA DI PT. X - Fitriany, Rany (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT UPI YPTK PADANG, 2019)
ABSTRACT   This study aims to see the effect of Coaching training to improve supervisor performance in the sales division at PT. X. Data collection uses performance scales, interviews and observations. The research design used was The One Group Pretest-posttest Design. Technical statistical analysis to test the hypothesis in this study using paired t-test (paired-sample T-test) and qualitative analysis to describe the effect of Coaching training to improve supervisor performance in the sales division at PT. X. The results of the study show that there is an effect of Coaching training to improve supervisor performance in the sales division at PT. X. (p <0.05). The form of influence is positive, which means that when the sales supervisor of the salesperson at PT X receives coaching training, the performance of the sales supervisor of the salesperson at PT. X gets positive changes related to its performance.   Keywords: Coaching training, performance and supervisor